Solid Lymph Nodes as an Imaging Biomarker for Risk Stratification in Human Papillomavirus–Related Oropharyngeal Squamous Cell Carcinoma - Rath, T.J. (AJNR Am J Neuroradiol, 2017)
BACKGROUND AND PURPOSE: Human papillomavirus–related oropharyngeal squamous cell carcinoma is associated with cystic lymph nodes on CT and has a favorable prognosis. A subset of patients with aggressive disease experience treatment failure. Our aim was to determine whether the extent of cystic lymph node burden on staging CT can serve as an imaging biomarker to predict treatment failure in human papillomavirus–related oropharyngeal squamous cell carcinoma. MATERIALS AND METHODS: We identified patients with human papilloma virus–related oropharyngeal squamous cell carcinoma and staging neck CTs. Demographic and clinical variables were recorded. We retrospectively classified the metastatic lymph node burden on CT as cystic or solid and assessed radiologic extracapsular spread. Biopsy, subsequent imaging, or clinical follow-up was the reference standard for treatment failure. The primary end point was disease-free survival. Cox proportional hazard regression analyses of clinical, demographic, and anatomic variables for treatment failure were performed. RESULTS: One hundred eighty-three patients were included with a mean follow-up of 38 months. In univariate analysis, the following variables had a statistically significant association with treatment failure: solid-versus-cystic lymph nodes, clinical T-stage, clinical N-stage, and radiologic evidence of extracapsular spread. The multivariate Cox proportional hazard model resulted in a model that included solid-versus-cystic lymph nodes, T-stage, and radiologic evidence of extracapsular spread as independent predictors of treatment failure. Patients with cystic nodal metastasis at staging had significantly better disease-free survival than patients with solid lymph nodes. CONCLUSIONS: In human papilloma virus–related oropharyngeal squamous cell carcinoma, patients with solid lymph node metastases are at higher risk for treatment failure with worse disease-free survival. Solid lymph nodes may serve as an imaging biomarker to tailor individual treatment regimens.